Pengaruh Edukasi Perilaku Vulva Hygine Dengan Media Video Dan Ceramah Terhadap Perilaku Vulva Hygine Pada Santriwati Rersiko Keputhan Patologis Di Pondok Pesantren Raudhatul Malikiyah Kota Probolinggo - Siti Linda Masluha; Handono Fathur Rohman; Agus Nurul Hidayat (Jurnal Keperawatan Muhammadiyah, 2021)
ABSTRACTBackground: Vulva hygine is necessary to prevent pathological vaginal discharge. The right strategy to prevent vaginal discharge is to provide Vulva hygine education. The study was conducted on April 1, 2020 for 1 week.Research methods: Using a quasi-experimental research method. This type of research is the pre and post test control group design with a sample of 65 respondents, using a questionnaire measuring instrument and using the Wilcoxon test for knowledge and attitudes and the T test for action.Results: statistical tests on knowledge and attitudes using the Wilcoxon test, from the results of these tests obtained results for knowledge and attitudes P value + 0.000 <α 0.05, and for action using the Paired sample T-test statistical test and the results obtained P value = 0.000 <α 0.05. This means that from the three domains above Ha is accepted.Conclusion: There is an effect of education on the knowledge, attitudes and actions of students at the risk of pathological vaginal discharge. Based on the results of this study, it is advisable for students to apply the education that has been given during the research. Keywords: Education, Vulva Hygine, Knowledge, Attitude, Action